(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
Impact of examination stress on psycho-physiological and cardiodynamic indicators of the students of 9–11th grades at school for gifted children of the city of Sari (IRI) was studied. It was determined that pre-examination emotional stress depends on age, gender and physiological characteristics of a person. Increased heart rate was registered for all teenagers, which was most prominent in male participants. This effect lasted after examination period too. Psycho-emotional stress of the examination period also impacted blood pressure with hyper sympathotony domination was registered.